Evaluating a new scale for infertility psychological distress: psychometric evidence from China - Lingjun Jiang; Liu Yang; Juan Yao; Juan Yang; Meiliyang Wu; Mengmei Yuan; Ke Zhang; Ye Chen; Zhenjing Hu; Zining Zhu; Qian Zhang; Meizhen Zhao; et al. (BMC Psychology)
Abstract Background China currently does not have a suitable tool to measure infertility-related psychological distress in a culturally relevant manner. Therefore, this study sought to develop and validate a scale specifically designed for the Chinese context, focusing on the unique cultural and psychological experiences of Chinese women undergoing IVF-ET treatment. Methods A mixed-methods approach was used for scale development. The preliminary scale was based on a previous Grounded theory study and existing literature. Content validity was assessed using the Delphi method. Psychometric testing involved 600 women undergoing IVF-ET treatment in Hubei, China. Item analysis, exploratory factor analysis (EFA), and confirmatory factor analysis (CFA) were conducted for scale refinement and validity assessment. Results The final scale consists of 25 items across 2 dimensions and 6 sub-dimensions: Distress of disrupting the former self (distress of self-worth questioning, distress of strained family relationships, distress of female image deficit) and Distress linked to the struggling present self (distress of inadequate reproductive self-efficiency, distress of maintaining family relationships, distress of social identity expansion). CFA confirmed a good fit for the 6-factor model. Cronbach’s alpha was 0.944 for the total scale, and 0.856 to 0.925 for the dimensions. Content validity was strong (I-CVI = 0.80-1.0, S-CVI = 0.98). The scale showed good criterion-related validity with a significant correlation (r = 0.528, p < 0.001) to the Kessler-6. Conclusion The Infertility Psychological Distress Scale demonstrates strong reliability and validity, accurately capturing the psychological distress experienced by women undergoing assisted reproduction in the Chinese cultural context. Clinical trial number Not applicable.